On P-Injective Modules And Ɣ-Regular Rings - Baida S. Abdullah (College of Education for Pure Sciences, 2012)
ABSTRACT The main purpose of this paper is to study Ɣ-regular rings, and the connection between such rings and weakly regular, π-regular, strongly π-regular, semi π-regular and SNI-rings. We also study P-injective modules, and to find it's relation with Ɣ-regular rings.